Knowledge Mobilization Through Continuing Education: Reflections on the Development of a Microcertificate in Trauma-informed Education - Reid, Nathalie; Schultz, Christie (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
This dialogue explores the development and implementation of a microcertificate in trauma‑informed/sensitive pedagogies and practices at the University of Regina. Through a conversation between Nathalie Reid, an assistant professor and director of the Child Trauma Research Centre, and Christie Schultz, dean of the Centre for Continuing Education, the discussion highlights the need for trauma‑informed practices in education and the process of translating research into practical, access‑ible professional development for educators who are themselves adult learners. The dialogue details the origins of the microcertificate, the partnerships that facilitated its creation, and the impact it has had on educators, students, and researchers. Key themes include the importance of co‑creation with stakeholders, flexibility in delivery methods, and the reciprocal relationship between research and practice. This dialogue underscores the potential of continuing education as a vehicle for knowledge mobilization, offering insights into effective strategies for bridging the gap between academic research and practice.